Batch fermentation and Simultaneous Saccharification and Fermentation (SSF) processes by Meyerozyma Guilliermondii Strain F22 and Saccharomyces cerecvisae for xylitol and bioethanol co-production - Shalsh, Dr.Fawzia; Dhoha Kadeem Nagimm; Muhammad Abdul Alrheem; Saffa Abedul Alrheem (Al-Qadisiyah Journal of Pure Science, 2021)
Recent years have seen an increase in the use of lignocellulosic materials in the development of bioproduct, biorefinery technologies have focused on process integration for the production of different valuable coproducts in order to reduce the overall processing cost. In this study, agricultural wastes from rice straw were used for the co-production of bioethanol and xylitol. Where bioethanol is produced from the cellulosic fraction and xylitol from the hemicellulose fraction after elimination of lignin using chemical pretreatments. The chemical treatment was carried out with diluted acid 2.5% at a 100 °C for 30 minutes , and then exposed the cellulosic fraction of the solid phase resulting from the chemical process to the enzymatic action of the fungus Trichoderma harzianum for releas sugars and fermented at a later stage using Saccharomyces cerecvisae for bioethanol production in a simultaneous saccharification and fermentation process, The liquid phase hemicellulose fraction was exposed to action of Meyerozyma guilliermondii strain F22 (Pichia guilliermondii) for xylitol production. Resulting was accomplished yielding maximum concentrations and product yield were 32.6 g/L 0.39g/g and 20.1 g/L, 0.44g/g for bioethanol and xylitol respectively of the total glucose and xylose available in rice straw, the co-production of xylitol with ethanol in an integrated biorefinery would create economic benefits making the overall lignocellulose-based process more cost effective